Can heart rate variability determine recovery following distinct strength loadings? A randomized cross-over trial - Thamm, A.; Freitag, N.; Figueiredo, P.; Doma, K.; Rottensteiner, C.; Bloch, W.; Schumann, M. (International Journal of Environmental Research and Public Health, 2019)
This study aimed to compare the acute effects of hypertrophic (HYP) and maximum strength (MAX) loadings on heart rate variability (HRV) and to compare possible loading-specific alterations with other markers of recovery. Ten young men with strength training experience performed two leg press loadings (HYP: five times 10 repetitions at 70% of one repetition maximum (1RM) with 2 minutes inter-set rest; MAX: 15 times one repetition at 100% of 1RM with 3 minutes inter-set rest) in a randomized order. The root mean square of successive differences statistically decreased after both protocols (HYP: 65.7 ± 26.6 ms to 23.9 ± 18.7 ms, p = 0.026; MAX: 77.7 ± 37.0 ms to 55.3 ± 22.3 ms, p = 0.049), while the frequency domains of HRV remained statistically unaltered. The low frequency (LF) band statistically increased at 48h post-MAX only (p = 0.033). Maximal isometric voluntary contraction (MVC) statistically decreased after HYP (p = 0.026) and returned to baseline after 24h of recovery. Creatine kinase (CK) statistically increased above baseline at 1h post-loadings (HYP p = 0.028; MAX p = 0.020), returning to baseline at 24h post. Our findings indicate no distinct associations between changes in HRV and MVC or CK.